Analisis Ketergantungan Impor Bahan Baku terhadap Kinerja Ekspor Industri Tekstil Indonesia Tahun 2025: Studi Perdagangan dengan Negara Asia - Muhammad Rafly (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study analyzes the dependence of imported raw materials on Indonesia’s textile export performance in 2025, focusing on trade with Asian countries such as China, India, and Korea Selatan. Using a descriptive quantitative and qualitative approach, the study finds that although exports remain strong, high import dependence reflects Indonesia’s role as an intermediate producer in the global value chain. This creates both opportunities for export growth and vulnerabilities due to external dependency.